2018
DOI: 10.14686/buefad.358488
|View full text |Cite
|
Sign up to set email alerts
|

Secondary School Students' Feedback on Course Processing and Collaborative Learning with Web 2.0 Tools-Supported STEM Activities

Abstract: The aim of our work is to develop STEM activities supported by Web 2.0 tools and to examine the opinions of the students about collaborative learning method. The study group consists of six girls and six boys from seventh class secondary school students of Konya Selçuklu Sancak Secondary School in 2016-2017. Necessary corrections on STEM activity, developed by the researchers, were made by taking the opinions of 3 field experts and 1 language expert. This research is a descriptive study in qualitative structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 5 publications
1
14
0
1
Order By: Relevance
“…This gave them an opportunity to see weakness versus strengths of their design solutions. This finding is consistent with the previous STEM studies in which collaboration has been emerged as prominent 21 st century skills that students acquired through the design process (Bolatlı & Korucu, 2018;Karakaya et al, 2019;Özcan & Koca, 2019;Özçelik & Akgündüz, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…This gave them an opportunity to see weakness versus strengths of their design solutions. This finding is consistent with the previous STEM studies in which collaboration has been emerged as prominent 21 st century skills that students acquired through the design process (Bolatlı & Korucu, 2018;Karakaya et al, 2019;Özcan & Koca, 2019;Özçelik & Akgündüz, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, many studies have been conducted, such as Shahzad et al (2020), Bolatli and Korucu (2018), and Yueh et al (2015) on participatory learning in e-learning environments, and these research and studies have proven the effectiveness of using participatory interaction patterns in increasing motivation, cognitive growth, and understanding among students. Sharing is a vital and effective component in learning environments based on the Web, as these studies have shown that patterns of electronic participation helped students get a high level of achievement.…”
Section: Figmentioning
confidence: 99%
“…In this respect, STEM education should be included in educational programs from early childhood education to higher education level (Aydagul & Terzioglu, 2014;Breiner et al, 2012;Bybee, 2010). Although STEM education practices are of great importance at primary, secondary and higher education levels (Bolatli & Korucu, 2018;Cotabish et al, 2013;Deveci, 2018;Gokbayrak & Karisan, 2017;Ince, Misir, Kupeli, & Firat, 2018;Park & Yoo, 2013;Ross & Gray, 2012;Robinson, 2016;Yildirim & Turk, 2018), the implementation of STEM education in early childhood is a matter of interest. Lots of questions have been raised, especially about the implementation of this kind of education in Turkey, so studies have been carried out (Akgunduz & Akpinar, 2018;Balat & Gunsen, 2017;Basaran, 2018;Cetinkaya-Aydin et al, 2017).…”
Section: Stem Education and Stakeholder's Opinionsmentioning
confidence: 99%
“…However, there is not enough research in this field in Turkey. The studies conducted so far emphasize the characteristics of STEM education (Arikan, 2018;Aydeniz, 2017;zamijeniti s Bahar et al, 2018;Yasar et al, 2018), teachers/prospective teachers' opinions on STEM education (Bakirci & Kutlu, 2018;Gulgun et al, 2017;Ozbilen, 2018;Ugras & Genc, 2018 ) or necessity and effects of STEM education on students at primary and high school levels (Bolatli & Korucu, 2018;Cotabish et al, 2013;Deveci, 2018;Gokbayrak & Karisan, 2017;Ince et al, 2018;Park & Yoo, 2013;Ross & Gray, 2012;Robinson, 2016;Yildirim & Turk, 2018). Studies on STEM education in early childhood are limited (Akgunduz & Akpinar, 2018;Balat & Gunsen, 2017;Basaran, 2018;Milford & Tippet, 2015;Tippett & Milford, 2017;Yasar Ekici et al, 2018).…”
Section: Stem Education and Stakeholder's Opinionsmentioning
confidence: 99%